Supporting Clinician-Scientist Development in Child Psychiatry: A Four-Domain Model for Individual or Programmatic Self-Reflection - Calhoun, Amanda; Herrington, Olivia D.; Leckman, James F.; Martin, Andrés (Frontiers in Psychiatry, 2021)
Background: The Albert J. Solnit Integrated Training Program (AJSP) is a novel educational initiative designed to prepare physician-scientists for independent careers in the investigation and treatment of childhood psychiatric disorders. Methods: We conducted a qualitative study to explore the impact and active components of the AJSP through hour-long individual interviews of its enrollees and graduates. We were specifically interested in identifying individual or programmatic traits for success that could be replicated elsewhere. As components of our theoretical framework, we used sources on Strength, Weakness, Opportunity, and Threat (SWOT) Analysis as applied to healthcare, and on mentorship and career development as pertaining to child and adolescent psychiatry (CAP). Results: Thirty-four individuals matriculated into the AJSP between 2004 and 2020, 33 (97%) of whom participated. Through iterative thematic analysis, we developed a model consisting of quadrants resulting from the intersection of a developmental perspective (spanning professional or personal spheres) and a reflective direction (with outward- or inward-facing vantage points). The model can be of practical utility through putative questions that trainees/program leaders could ask themselves by using the four domains as points of departure: (I) Individual: “Is becoming a clinician-scientist right for me?”/“What traits are we looking for in prospective applicants?”; (II) Program: “Is this the right program for me?”/“What is the right balance between structure and freedom for trainees to thrive in?”; (III) Mentorship: “What is the right number and constellation of mentors for me?”/“How can we optimize our experience and backgrounds toward the benefit of our trainees?”; and (IV) Charting Course: “Who do I want to become?”/“How can we help our charges embrace, find, or reconnect with their true vocation?” Conclusion: Our analytic approach can help identify, refine, and replicate programs that are urgently needed to increase the workforce of clinician-scientists dedicated to improving the well-being and mental health of children and families. The model we describe can be fruitfully applied to the self-reflection by individuals or program leaders. Although based on a single program with very specific goals, the model could also be applied to other training initiatives within psychiatry—and beyond.